Analysis of the training objective corresponding to the Modern Languages academic program at ECCI University based on students of last semester perception (2021)
Abstract This monograph analyzes the objective of training and professional profile of the Modern Languages career of the ECCI University through a descriptive qualitative research, which is developed using two instruments (Regnier's Abacus and the interview) applied to last semester students, who, based on their experience, show the influence of interdisciplinarity on the occupational profile. In addition, the implementation of strategies is carried out with the interest of providing an improvement plan to the aforementioned career. Résumé Cette monographie analyse l'objectif de formation et le profil professionnel de la carrière des Langues Modernes à l'université ECCI à travers une recherche qualitative descriptive, qui est développée à l'aide de deux instruments (Abaque de Régnier et l'interview) appliqués à aux étudiants du dernier semestre, qui sur la base de leur expérience permettent l'influence de l'interdisciplinarité sur le profil professionnel est évident. De plus, en œuvre des stratégies est effectué avec l'intérêt de fournir un plan d'amélioration de la carrière susmentionné.